Religion as an effective tool in forestry practices, wildlife management and environmental sustainability in Kogi state, Nigeria (2018)
This paper examined religion as an effective tool in forestry practices, wildlife management and environmental sustainability in Nigeria. The roles of forestry and wildlife management in environmental sustainability are very imperative. This study was carried out in Kogi State, Nigeria. Data were obtained from Seven (7) randomly selected Local Government Areas (LGAs) within Kogi State. Structured questionnaire, direct field observation, and personal interview were used to collect information from indigenous people within the Study Area. Structured questionnaire was administered on Thirty (30) randomly selected respondents from each of the LGAs making a total number of Two hundred and Ten (210) respondents. The data was subjected to descriptive and inferential statistical analysis such as table and graph; and parametric statistics, respectively. The results showed that there were Thirty-Nine (39) sacred forests, Twenty-Five (25) burial ground forests, and Seven (7) plantation forests in the Study Area. The results also showed that One-Hundred and Sixty-three (163) out of Two-Hundred and Ten (210) respondents are of the view that religion can be used to prevent deforestation, wildlife destruction, and environmental degradation. The inferential analysis using student’s t-test and ANOVA shows significant differences which implies that most of the respondents accept religion as an effective tool to reduce forest and wildlife destruction, and also that the sacred forests are the most preserved forests in the Study Area. Therefore, involvement of all stakeholders, religious leaders and their followers in sustainable forest/wildlife management and environment sustainability will go a long way to reduce deforestation, desertification, and extinction of some trees/shrubs/wild plants, wild animals, and environmental degradation.